2021
DOI: 10.1097/phm.0000000000001713
|View full text |Cite
|
Sign up to set email alerts
|

Short Walking Exercise Leads to Gait Changes and Muscle Fatigue in Children With Cerebral Palsy Who Walk With Jump Gait

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Recent studies in children with CP reported changes of the gait pattern towards more knee flexion during the early stance phase accompanied by signs of muscle fatigue after a 6-minute walking exercise (6MW) in children who walk in a crouched 8,9 or jump gait pattern. 10 This supports the idea that gait deviations progress with prolonged walking because of physical fatigue. Moreover, because minimization of ECoW is an important criterion for gait pattern optimization, 11 the results of these studies raise the question whether gait pattern changes that occur after prolonged walking would also result in a further increase in ECoW in children with CP.…”
supporting
confidence: 74%
“…Recent studies in children with CP reported changes of the gait pattern towards more knee flexion during the early stance phase accompanied by signs of muscle fatigue after a 6-minute walking exercise (6MW) in children who walk in a crouched 8,9 or jump gait pattern. 10 This supports the idea that gait deviations progress with prolonged walking because of physical fatigue. Moreover, because minimization of ECoW is an important criterion for gait pattern optimization, 11 the results of these studies raise the question whether gait pattern changes that occur after prolonged walking would also result in a further increase in ECoW in children with CP.…”
supporting
confidence: 74%
“…CP is a clinical diagnosis based on symptoms and neurological signs, and a definite diagnosis is usually made between 12 and 24 months of age, but a review of the progress in early diagnosis and treatment of CP published in JAMA Pediatrics in 2017 combs the standardized tools for early prediction of CP and clearly proposes that the time of diagnosis can be advanced to before 6 months of gestational age [ 20 ]. Study reported that the incidence of CP is 1‰~5‰ in the world, 2‰~3‰ in developed countries, and 1.8‰~4‰ in China [ 21 ]. CP is the most common physical disability in children, with 2.1 cases per 1000 cases in high-income countries [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We select two representative frequency domain characteristics, namely average power frequency f mean and median frequency f m f [56] defined as follows:…”
Section: Feature Extraction Of Semg Signalsmentioning
confidence: 99%